PENGARUH PERAN HORMON TERHADAP PSIKOLOGI DAN FISIOLOGI IBU BERSALIN - Pratista, Sevhania; Triwahyuningsih, Ria Yulianti; -, Tonasih; Musfiroh, Sri Musfiroh; Ainsani, Bela Ainsani; -, Ismayanti; Rezani, Nadia Rezani; Cholishah, Fajrin Nur Cholishah (Universitas Prima Indonesia, 2023)
Childbirth is physiologically a natural process and a tremendous phenomenon in a woman's life in order to adapt to motherhood. Naturally, maternity mothers will expend a lot of energy that causes changes in both physiological and psychological aspects. These changes are certainly dominated by the presence of hormones that help in the labor process. The purpose of this study is useful for analyzing and reviewing journals that have discussed the influence of hormones, psychology, and physiology on maternity mothers. The type of research used is Literature Review sourced from the Publish or Perish application with Google Scholar and Pubmed databases. The results obtained in the study show that hormones affect psychology and physiology during labor.